KAJIAN SEDIMEN TRANSPOR DAN PERUBAHAN MORFOLOGI SUNGAI OPAK PASCA ERUPSI GUNUNGAPI MERAPI TAHUN 2010 - , RONA MENTARI KUSUMA HATI; , Dr. Danang Sri Hadmoko, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Opak River is one of main river located on Merapi Volcano flank flowing sediment material source from eruption product. Sedimentation process can extend either benefit or loss impact for environment. Morphologycal component of river can change by presence of sediment source and influence on agradation and degradation of base flow. Objectives of this research were : explaining the spread of bed load material on Opak River at some partial elevation, analizing suspended sediment concentration transported at both flooding and normal flow condition, and determining morphologycal changes with appeal condition before and after 2010 Merapi Volcano eruption. Type of this research was observational research. It was designed with the graph, descriptive, and statistic analysis. Sample which had been monitored were at five observation area of Opak River fragment. They were sediment concentration flowed in river stream, flow discharge, and bed load material which spreaded on river fragment. Result of this study examined disavowal with hypothesis that in higher elevation would bigger in material size. In that case, the existence of Sabo DAM along Opak River had possesed bed load material spreading. Suspended sediment rating curve at normal flow at three observation area as follow : Cs=1,012 (Q)0,034 , Cs=1,033 (Q)0,023, Cs=1,043(Q)0,00357. At flood condition, daily sediment discharge rate was 111,4 ton/day for flooding in January, and as much as 1800,46 ton/day for flooding in February. Result equivalent of river cross section year 2000 and 2013 in Ngablak Village showed some changes although they were not significant. That changes were degradation at right side of channel, and agradation at left side and middle of channel. Efforts necessary to be done in Opak River management are : monitoring river stream condition periodically and taking some material along the stream in order to flowing water unavoidably through the stream.